Should International Law Ensure the Moral Acceptability of War? - Dill, J (Cambridge University Press, 2013)
Jeff McMahan's challenge to conventional just-war theory is an attempt to apply to the use of force between states a moral standard whose pertinence to international relations (IR) is decreasingly contestable and the regulation of which international law (IL) is, therefore, under pressure to afford: the preservation of individual rights. This compelling endeavour is at an impasse given the admission of many ethicists that it is currently impossible for international humanitarian law (IHL) to regulate killing in war in accordance with individuals' liability. IHL's failure to consistently protect individual rights, specifically its shortfall compared to human rights law, has raised questions about IHL's adequacy also among international lawyers. This paper identifies the features of war that ground the inability of IL to regulate it to a level of moral acceptability and characterizes the quintessential war as presenting what I call an 'epistemically cloaked forced choice' regarding the preservation of individual rights. Commitment to the above moral standard, then, means that IL should not prejudge the outcome of wars and must, somewhat paradoxically, diverge from morality when making prescriptions about the conduct of hostilities. In showing that many confrontations between states inevitably take the form of such epistemically cloaked forced choices, the paper contests the argument by revisionist just-war theorists like McMahan that the failure of IL to track morality in war is merely a function of contingent institutional desiderata. IHL, with its moral limitations, has a continuing role to play in IR.